His to claim - Jackson, Brenda (Brenda Streater) (Jackson, Brenda (Brenda Streater). Westmoreland legacy., 2019)
When navy SEAL and honorary Westmoreland Mac McRoy returns home, he discovers his wife has left. Teri has retreated to the Wyoming ranch they<U+2019>d planned to visit together, and is resentful when he follows. She doesn<U+2019>t want a second honeymoon; she wants a marriage Mac doesn<U+2019>t take for granted. But life-or-death circumstances are about to put their love to the ultimate test.